Status and determinants of health literacy: a study among adult population in selected areas of Myanmar - Oo, Win M.; Soe, Pa P.; Lwin, Kay T. (International Journal Of Community Medicine And Public Health, 2017)
Background: Health literacy means cognitive and social skills of an individual that determine his or her ability to access, understand and use health information in order to promote and maintain good health. Health literacy is important not only for health but also for socioeconomic development because limited health literacy increases health care cost. Objective: To determine the status and determinants of health literacy, and association between health literacy and health-risk behaviours among Myanmar population. Methods:A cross-sectional study was conducted among 1367 adults. Multi-stage random sampling was applied. Data entry and analysis was done using Stata 11.0 statistical package. Results: The prevalence of satisfactory, intermediate and poor health literacy were about 31.5% (95% CI: 29.1%, 34.1%), 40.3% (95% CI: 37.7%, 43.0%), and 28.2% (95% CI: 25.8%, 30.6%), respectively. Age, sex, marital status, education, sufficiency of expenditure, watching medical-related TV series, accessibility to education & health education courses, ability to pay for medication and affordability to see medical doctors were detected as significant determinants of health literacy. Health literacy was also significantly related to health-risk behaviors such as smoking, betel chewing, and not taking regular exercise. There was marginal association between health literacy and alcohol drinking (p = 0.064). Conclusions:The present study encourages efforts to improve health literacy in the Myanmar adults by enhancing health education and health promotion activities. It is also important to improve their socio-economic status.